Detection of blade substrate crack parameters of hard-coated blisk based on mistuning identification technology. (15th February 2022) - Xu, Kunpeng; Yan, Xianfei; Xu, Dalu; Du, Dongxu; Sun, Wei
Highlights: A crack detection method based on mistuning identification technique is proposed. Size and location of blade substrate crack for hard-coated blisk are detected. Crack parameters of all blades can be detected at one time, it's high-efficiency. Numerical and actual cases show the effectiveness of this detection method. The method has a high accuracy for cracks in a specific length and location range. Abstract: The detection of blade substrate crack is crucial for the safe operation of hard-coated blisk. Due to the coating coverage, it tremendously increases the difficulty of crack size and location detection. This paper presents a novel method based on the mistuning identification technique to detect the blade substrate crack parameters (including crack size and location) for the hard-coated blisk. Different from previous studies, the stiffness mistuning caused by substrate crack is taken as the quantitative parameter to detect crack parameters in this method. A method to identify the stiffness mistuning of blade substrate crack using only modal data is presented based on the reduced- order model of blisk. The basic data sets of substrate crack stiffness mistuning need to be established by finite element simulation. The crack mistuning basic data sets and crack mistuning under the first and second bending modal families are matched to determine the crack parameters. A crack detection procedure is presented based on these theories. The effectiveness of the detection method is verified by numerical and real cases. The results show that the method can effectively detect the crack parameters of all blades at one time, which has high detection efficiency. It also appears that the detection accuracy of the crack location is higher than that of the crack size. Finally, the rule of the detection accuracy changing with the crack parameters is studied. The results show that the proposed method has a good and stable identification accuracy for cracks in a specific size and location range.